Introduction: Film adaptation in the post-cinematic era. (1st July 2014) - Kilbourn, Russell J. A.; Faubert, Patrick
In recent years, adaptation studies has emerged as a field of urgent scholarly importance and, having moved past outdated presuppositions and prejudices, has revealed adaptation as a crucial form of dialogue between and among different media, texts and social–historical contexts. The proliferation of new technologies and new media, theorized as the digital post-cinematic era, but encompassing more than what Costas Constandinides calls the 'post-celluloid' (2010: 3), has arguably deepened this importance, implicating adaptation in previously unconsidered cultural arenas. In their common emphasis upon post-millennial cinema, all four articles in this dossier are based in the recognition that it is no longer possible to conceive of filmic adaptation as a straightforward movement from page to screen; that therefore we must turn our attention to the role new media technologies play in processes of dialogic mediation and identity formation, in the production (and elision) of inter-subjective and cultural difference, in the shaping of cultural memory, and in the very question of defining cinema in the early twenty-first century.